New explicit solutions for Zakharov-Kuznetsov-Benjamin-Bona-Mahony equation - Yue Ren (Journal of Applied Science and Engineering, 2024)
In this paper, we propose two techniques for constructing new explicit exact (EE) solutions of the the ZK-BBM equation. we utilize either the modified Kudryashov technique and a new Kudryashov technique in conjunction with symbolic computation to achieve this goal. In addition, 3D and 2D plots were generated to illustrate the features of the obtained solutions. This was achieved by meticulously choosing appropriate values for the relevant parameters. The results determine that these techniques are a mighty math instrument to solve nonlinear partial differential equations (NLPDEs) in terms of efficiency, validity and accuracy.